VALIDATION OF A CONSTRUCT TO IDENTIFY THE IMPACT OF AUTONOMY LEVELS, LEADERSHIP STYLES AND CONSCIOUSNESS LEVELS IN WORK TEAM’S PERFORMANCE ON THE SHOP FLOOR - de Oliveira, Leonardo Canesso; Cordeiro, José Vicente Bandeira de Mello (Caderno PAIC, 2018)
Studies about work teams have been developed over time, growing in recent years. As we know, there are variables that can impact an organization’s teams and their performance. Cordeiro has been developing a study over the years that correlates leadership, autonomy and consciousness levels. Therefore, this research has the objective of developing and validating a construct to identify the impact of leadership profiles, team’s autonomy levels and team members’ consciousness levels on teams’ performance. To achieve this goal, two questionnaires were formulated (one for leadership and one for autonomy), using Google Forms to build it. The leadership questionnaire was based on Goleman’s studies, while the autonomy questionnaire was based on Bastos and Cordeiro recent studies. The Sphinx software was used to alidate the questionnaires, aiming to verify a Cronbach Alpha higher than 0,6, which makes it possible to validate the construct. With a 0,72 Cronbach’s Alpha for leadership and 0,92 for autonomy, the main goal of this research was achieved, validating the construct. The next step for further research is to verify in practical terms the three variables correlation on the shop floor of industries located in metropolitan region of Curitiba – PR, using the construct as a tool for a quantitative research.